Observación y análisis de la variación de parámetros geofísicos de un pozo ubicado en el piedemonte llanero - Montano Mejía, Felix Humberto (Earth Sciences Research Journal, 2001)
This paper shows geophysical characterization near a shallow well located in the Llano University (Villavicencio), which was conveniently selected because it's Piedemonte L1anero proximity, zone characterized by a very active fault system. The specialized instrumentation development is also described that was designed and started up to carry out a telemetry observation using a multiparameter remote station located near the well under observation and one local station in the National University of Colombia (Bogota) from where geophysical parameters variations an analysis are permanently monitored.